PEMBERDAYAAN MASYARAKAT SEBAGAI UPAYA PEMANFAATAN INSENERATOR DALAM MENGELOLAH SAMPAH ANORGANIK - Mariene Wiwin Dolang; Zulfikar Lating; Abd. Rijali Lapodi; M. Taufan Umasugi (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
Garbage is one of the factors causing environmental damage in Indonesia. Although many people understand the consequences of piling up garbage, in fact the waste problem has not become a top priority to be solved. Waste will increase along with the increase in population and the level of public consumption and other activities. The reality that is happening now is only the "transfer" of waste, not waste management. Tehoru Village is one of the villages where the majority of households do not have trash cans and throw garbage around the house. In the morning and evening, residents who act as housewives clean the garbage around their homes by sweeping them. After the garbage has been collected, the action taken is to burn the collection of garbage or some of the residents throw the garbage at the village waste collection point located at several points in the village settlement area. Seeing the problems that exist in Tehoru village, the first and second partners work together to make incinerators that can be used to burn waste and reduce the volume of waste and air pollution. However, what needs to be emphasized in the development of incinerators is that incinerators are not the main solution to solving the waste problem. Incinerator is just a tool to destroy existing waste. The main solution to solve fixed waste by implementing 3R (Reduce, Reuse, Recycle)